Transformasi SDM Kesehatan melalui Manajemen Talenta di Rumah Sakit: Literature Review - Sosiawan, Putu Prathiwi Kemala Putri; Walean, Ayu Kezia; Sumarauw, Christine Dianne; Paramarta, Vip (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Human resources (HR) in healthcare play a crucial role in determining the quality, safety, and sustainability of hospital services. As the healthcare sector undergoes rapid changes driven by digital transformation, increasing service complexity, and rising patient expectations, talent management has emerged as a strategic necessity for hospital organizations. This literature review aims to analyze the role of talent management in transforming the healthcare workforce by synthesizing findings from scientific articles published between 2018 and 2025. Databases including Scopus, PubMed, ScienceDirect, and SINTA were reviewed using keywords related to talent management, healthcare workforce development, leadership succession, and hospital human resource strategies. The results indicate that talent management significantly enhances workforce competence, leadership capabilities, digital readiness, job satisfaction, and employee retention. It also contributes to reducing burnout, strengthening organizational culture, and improving interdisciplinary collaboration—factors essential for patient safety and service excellence. Moreover, talent management supports the adoption of digital health technologies by improving digital literacy among healthcare workers. However, several challenges persist, particularly in the Indonesian context, such as limited HR information systems, insufficient talent mapping, resistance from senior staff, and inadequate investment in digital training. Overall, this review highlights that talent management is not merely an HR function but a strategic driver of hospital performance and long-term sustainability. Integrating talent management into hospital planning, leadership development, competency assessment, and career pathways is essential to building an adaptive, innovative, and high-performing healthcare workforce capable of meeting future health system demands.